Investigation of some solvents for asphalten-wax-paraffin depositions formed on the oil refinery equipment - Тертишна, О. В. (Proceedings of National Aviation University (archive), 2013)
Тhe methods of asphalten - wax- paraffin depositions removal from the oil refinery equipment were studied. The effectiveness of solvents were estimated by mass losses of samples wrapped up in filter paper after exposition in different reagents, such as once-run petrol, benzene, toluene, hexane and some mixtures of these substances. The best results were obtained in the hexane - benzene mixture with volume ratio 1:1. The maximal level of dissolution was achieved at 30-35 °С